2018
DOI: 10.1177/2045894018799738
|View full text |Cite
|
Sign up to set email alerts
|

Safety and long‐term efficacy of AAV1.SERCA2a using nebulizer delivery in a pig model of pulmonary hypertension

Abstract: Nebulization delivery of adeno-associated virus serotype 1 encoding sarcoplasmic reticulum Ca2+-ATPase2a (AAV1.SERCA2a) gene was examined in a Yukatan miniature swine model of chronic pulmonary hypertension (n = 13). Nebulization of AAV1.SERCA2a resulted in homogenous distribution of vectors, lower pulmonary vascular resistance, and a trend towards better long-term survival compared to control animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 7 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…In a prevention protocol, AAV1.SERCA2a delivery attenuated adverse hemodynamic profiles as well as indices of pulmonary and cardiac remodeling in comparison with rats administered with AAV1 carrying β-galactosidase or saline. More recently, safety and long-term efficacy of AAV1.SERCA2a using nebulizer delivery has been examined in a Yukatan miniature swine model of chronic pulmonary hypertension ( Watanabe et al, 2018 ). Similar to Yorkshire pigs, Yukatan miniature swine developed PH two months after the pulmonary vein banding surgery, as demonstrated by elevated pulmonary pressures, increased vascular resistance, and RV failure.…”
Section: Emerging Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prevention protocol, AAV1.SERCA2a delivery attenuated adverse hemodynamic profiles as well as indices of pulmonary and cardiac remodeling in comparison with rats administered with AAV1 carrying β-galactosidase or saline. More recently, safety and long-term efficacy of AAV1.SERCA2a using nebulizer delivery has been examined in a Yukatan miniature swine model of chronic pulmonary hypertension ( Watanabe et al, 2018 ). Similar to Yorkshire pigs, Yukatan miniature swine developed PH two months after the pulmonary vein banding surgery, as demonstrated by elevated pulmonary pressures, increased vascular resistance, and RV failure.…”
Section: Emerging Therapiesmentioning
confidence: 99%
“…Similar to Yorkshire pigs, Yukatan miniature swine developed PH two months after the pulmonary vein banding surgery, as demonstrated by elevated pulmonary pressures, increased vascular resistance, and RV failure. The authors assessed the therapeutic efficacy of nebulized AAV1.SERCA2a at two months after delivery and found that nebulized AAV1.SERCA2a gene therapy significantly decreased pulmonary vascular medial thickness, pulmonary vascular resistance, and increased long-term survival compared to control animals ( Watanabe et al, 2018 ).…”
Section: Emerging Therapiesmentioning
confidence: 99%
“…While the injected cells were short lived in the lungs (<24 h), the injected animals showed an immediate increase in BMPR2 in their lungs, which was thought to be exosome mediated, as well as an improvement in muscularized vessels over time [ 52 ]. Another avenue to overcome the obstacle of a neutralizing immune response would be the use of Adeno-associated virus (AAV) for gene delivery, which elicits only a neglectable immune response [ 53 , 54 ]. The use of the adenovirus for BMPR2 AAV1.SERCA2a reduced RV hypertrophy, RVSP, mPAP and vascular remodeling, thereby overall reducing experimental PH [ 55 ].…”
Section: Therapeutic Strategies To Modify Bmpr2 Signalingmentioning
confidence: 99%
“…5 , 8 The Optineb® nebulizer device that is used with PH treatment inhaled pharmaceutical product Tyvaso® is an ultrasonic nebulizer device. 6 In the paper by Hajjar et al., 9 the authors investigated the safety and efficacy of nebulized gene delivery.…”
mentioning
confidence: 99%
“…Promising results were reported. 9 Pulmonary vascular resistance was lowered and long-term survival was increased. Imaging showed the distribution of the aerosol in the lungs.…”
mentioning
confidence: 99%